Legal Protection for the LGBT Community in the Era of Inclusive Digital Transformation in Indonesia (Open Society Conference, 2025)
This study aims to analyze the legal protection for the LGBT community in Indonesia amidst the era of inclusive digital transformation. Employing a normative legal research method, the study examines the existing legal framework, including the 1945 Constitution and Law No. 1 of 2024 on the Second Amendment to Law No. 11 of 2008 on Information and Electronic Transactions (the ITE Law), as well as the challenges and loopholes in its implementation. The findings reveal that current legal protection is partial and ineffective, primarily due to the absence of regulations that explicitly include sexual orientation and gender identity as categories protected from discrimination. The phrasing of articles in the ITE Law is deemed overly general, and its application is often hindered by bias among law enforcement officials, which makes victims of cybercrimes such as cyberbullying and doxing particularly vulnerable. This research concludes that comprehensive measures are needed, ranging from revising the ITE Law and providing training for law enforcement, to collaborating with digital platforms and launching public education campaigns, in order to create a legal and social ecosystem that is truly inclusive and non-discriminatory.